ULASAN ARTIKEL ILMIAH ASSESING THE QUALITY OF ARGUMENTS IN STUDENTS’ PERSUASIVE WRITING - Adara, Reza Anggriyashati (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2017)
This review critically analyses research methodologies of two research articles (RA) which titled Assessing the quality of arguments in students? persuasive writing: A case study analysing the relationship between surface structure and substance by Stapleton and Wu (2015) and Disciplinary and ethnolinguistic influences on citation in research articles by Hu and Wang (2014). Whereas Stapleton and Wu (2015) used Toulmin model and questionnaires to gather data, Hu and Wang (2014) applied CBA (Corpus-Based Approach). Although methodologies used in both RAs are suitable for the research, the questionnaires used in Stapleton and Wu (2015) will gather better result with slightly different wording. Besides analysing the methodologies, the review also discusses the implications of those RAs to EAP teaching